1984
DOI: 10.1021/bi00308a001
|View full text |Cite
|
Sign up to set email alerts
|

Photoaffinity labeling of DNA-dependent RNA polymerase from Escherichia coli with 8-azidoadenosine 5'-triphosphate

Abstract: A photoaffinity analogue of adenosine 5'-triphosphate (ATP), 8-azidoadenosine 5'-triphosphate (8-N3ATP), has been used to elucidate the role of the various subunits involved in forming the active site of Escherichia coli DNA-dependent RNA polymerase. 8-N3ATP was found to be a competitive inhibitor of the enzyme with respect to the incorporation of ATP with Ki = 42 microM, while uridine 5'-triphosphate (UTP) incorporation was not affected. UV irradiation of the reaction mixture containing RNA polymerase and [ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The finding that more than one component of the channel is photolabelled is not unusual as photoaffinity ligands are known to incorporate into more than one subunit of oligomeric enzymes and hormoneor neurotransmitter receptors (e.g., Hall and Ruoho, 1980;Woody et al, 1984;Yip et al, 1980). This proves that A, B and C decay as independent targets and must be present as such in the membrane.…”
Section: Discussionmentioning
confidence: 97%
“…The finding that more than one component of the channel is photolabelled is not unusual as photoaffinity ligands are known to incorporate into more than one subunit of oligomeric enzymes and hormoneor neurotransmitter receptors (e.g., Hall and Ruoho, 1980;Woody et al, 1984;Yip et al, 1980). This proves that A, B and C decay as independent targets and must be present as such in the membrane.…”
Section: Discussionmentioning
confidence: 97%
“…They also indicate that the actual ATPbinding component is probably not hsp90, but is likely to be hsp70 or possibly the progesterone receptor proteins themselves, since the binding of progesterone receptor to ATPSepharose has been demonstrated (34). To determine which protein in the receptor complex was binding ATP, we photolabeled the complex with 8-azido[32P]ATP, an effective affinity-labeling agent used in several systems to define ATP-binding proteins (1,2,67). Preliminary studies showed that this ATP analog was bound in a saturable, Mn-dependent manner.…”
Section: Methodsmentioning
confidence: 99%
“…Since one of our objectives was to synthesize a photoactive nucleotide analog that would serve as a substrate for DNA synthesis, the allowable modifications were further restricted to those that do not alter the normal anti conformation of the nucleotide. Substituents at the C8 position of purines and the C6 position of pyrimidines usually shift the normal anti conformation toward a syn conformation (16) that renders the nucleotide unacceptable as a substrate for E. coli DNA polymerase I (17) and other template-directed polymerases (7,18,19). Because of this restriction the 8-azidopurine nucleotide analogs are not substrates for template-directed enzymatic synthesis of DNA or RNA.…”
Section: Resultsmentioning
confidence: 99%